Implementing immersive virtual reality: Lessons learned and experience using open source game engine - Zainudin A.R.R.; Yusof A.M.; Rusli M.E.; Yusof M.Z.M.; Mahalil I. (Institute of Electrical and Electronics Engineers Inc., 2023)
This paper share in details the experiences gained during the development of a Virtual Reality application for a stress treatment. Throughout the twelve months development period, authors have faced numerous challenges and difficulties. Those challenges are encountered while setting up an open source game development platform called Cryengine and while integrating this engine with VR gadgets such as Kinect, audio system, Razer hydra, and Head Mount Display (HMD). This paper also discusses the solution for each of this problem. Note that a stress treatment will not be included because it is outside the scope of this paper. © 2014 IEEE.